Accommodation Industry its Strategic Business Practices that Survive in Times of Crisis - Andias, Amiel B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study examined the accommodation industry: its strategic business practices that survive in times of crisis of Dipolog City Zamboanga del Norte. The qualitative case study methodology employed to obtain an in-depth investigation of the real-time experiences of the research participants. The study anchored on Fred R. David's (2021) five strategic business management practices: leadership, people, operations, marketing, and financial performance. The study revealed that accommodations industry practicing democratic forms of leadership, hiring of employees based on skills, providing motivations to their employees, operating their business by giving customer satisfaction, advertising their products and services, and ensuring that they attain financial stability. Despite the size of these enterprises, they still carried out sustainability practices that revolve around social, economic, and environmental practices that corporate social responsibility. The study also found out that accommodation industry challenges imposed by external and internal factors. In order to survive the challenges, Accommodation Industry employed business-level strategies to develop competitive advantage in the market. It therefore recommended that accommodation industry develop and strengthen their strategic practices taking into consideration their corporate social responsibility.